Diskursus Kosmopolitanisme dalam Film Indonesia Berlatar Luar Negeri - Primadewi, Nerfita; Widiastutieningrum, Sri Rochana; Soetarno, Soetarno; Sugiharto, Ignatius Bambang (Institut Seni Indoensia Surakarta, 2023)
This research wants to see how locations, especially overseas locations are interpreted in scientific articles. The purpose of this study is to see how the meaning of location in Indonesian films is discussed academically outside of its function as an entertainment medium. The methodology used in this research is literary study. This method includes collecting data from various sources such as books, scientific articles, and press releases of Indonesian film using overseas location, and data analysis to determine how cosmopolitanism discourse appears in Indonesian films. This research underscores the importance of considering films as a representation of the desires of Indonesian audiences through the choice of locations chosen and how these locations function in the cinematic narrative.